Evaluation of the schistosomicidal efficacy of liposome - Entrapped Oxamniquine - Frédéric Frézard; Alan Lane de Melo (Revista do Instituto de Medicina Tropical de São Paulo, 1997)
Oxamniquine (OXA) was sucessfully encapsulated in small unilamellar vesicles using a pH gradient method. This procedure led to a high drug encapsulation efficiency (> 85%) at a drug to lipid molar ratio of 1/10. Moreover, these liposomes were found to retain encapsulated OXA efficciently under dialysis conditions at 37º C. Liposome-entrapped OXA (LOXA), OXA, and empty liposomes were tested against Schistosoma mansoni in a murine model. LOXA produced a significant reduction of the worm burden compared to the other preparations, when inoculated by subcutaneous route (s.c.) with 10 mg OXA/kg animal one day before the infection, and 3, 7, and 14 days after. However, LOXA was not effective when given 7 days before, or 35 days after infections. OXA, in the free form, was effective in relation to the untreated group, only when administered 3 days after the infection. Maximum effect of LOXA, with 97% reduction of the parasite number, was observed when the preparation was given s.c.one day before the infection. On the other hand, LOXA inoculated intraperitoneally one day before the infection didn’t show any reduction of the parasite count. It can be concluded that LOXA is more effective than OXA for the treatment of experimental schistosomiasis, particularly when administered subcutaneously at a time close to the infection Avaliação da eficácia esquistossomicida da oxamniquina encapsulada em liposomas. Oxamniquina (OXA) foi encapsulada em vesículas unilamelares pequenas de distearoilfosfatidilcolina usando-se técnica de encapsulação ativa em gradiante de pH. Este procedimento produziu uma alta eficiência de encapsulação (> 85%) com uma razão molar de 1/10, além de reter, eficientemente, a droga encapsulada sob condições de diálise à 37º C. OXA encapsulada (LOXA), OXA livre (OXA), (10 mg/kg respectivamente) ou liposomas vazios foram testados durante o curso da infecção experimental pelo Schistosoma mansoni. Verificou-se uma redução significativa do número de parasitos recuperados no grupo tratado com LOXA, por via ...